2018
DOI: 10.1299/jfst.2018jfst0002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diffusing layer thickness on the density-driven natural convection of miscible fluids in porous media: Modeling of mass transport

Abstract: In this study, density-driven natural convection in porous media associated with Rayleigh-Taylor instability was visualized by X-ray computed tomography to investigate the effect of the thickness of the diffusing interface on convection. The thickness of the interface was changed by molecular diffusion with time, and the effective diffusivity in a porous medium was estimated. Compared with the thick interface, for the thin interface, many fine fingers formed and extended rapidly in a vertical direction. The on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
(107 reference statements)
3
5
0
Order By: Relevance
“…As shown, the downwelling velocity linearly decays with Pe / Ra as ⟨⟩wdub1=A()italicPe/italicRa+B, with the fitted coefficients being A = − 0.166 ± 0.060 and B = 0.377 ± 0.032 (dashed line, R 2 = 0.79). We note that for three‐dimensional natural convection in a packed bed and in the absence of horizontal flow, Wang et al (2016) who also used a MEG solution (albeit doped with NaI) found that ⟨⟩wdub1=0.35, while Wang et al (2018) who used a system of pure water and brine doped with NaI found that 0.17<⟨⟩wdub1>0.5, in agreement with our results. The linear relation can be rearranged to represent the effect of the horizontal water velocity and the vertical gravitational velocity on the downwelling velocity of the fingers as ⟨⟩wd=ub()APeRa+B=0.3770.25emub0.1660.25emv.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As shown, the downwelling velocity linearly decays with Pe / Ra as ⟨⟩wdub1=A()italicPe/italicRa+B, with the fitted coefficients being A = − 0.166 ± 0.060 and B = 0.377 ± 0.032 (dashed line, R 2 = 0.79). We note that for three‐dimensional natural convection in a packed bed and in the absence of horizontal flow, Wang et al (2016) who also used a MEG solution (albeit doped with NaI) found that ⟨⟩wdub1=0.35, while Wang et al (2018) who used a system of pure water and brine doped with NaI found that 0.17<⟨⟩wdub1>0.5, in agreement with our results. The linear relation can be rearranged to represent the effect of the horizontal water velocity and the vertical gravitational velocity on the downwelling velocity of the fingers as ⟨⟩wd=ub()APeRa+B=0.3770.25emub0.1660.25emv.…”
Section: Resultssupporting
confidence: 91%
“…As seen in Figures 6a and 6b, the number of fingers decreases with time during the experiments. This was mostly due to the merging of small fingers into bigger ones during finger propagation, as observed in previous numerical and experimental studies (e.g., Riaz et al, 2006;Wang et al, 2018). The decrease in the maximum number of fingers with increasing water flow rate, shown in Figure 6b, is consistent with the simulations of Emami-Meybodi (2017) who found that a large horizontal velocity and the presence of high longitudinal dispersion lead to the formation of fewer fingers.…”
Section: The Fingers Spatial Distributionsupporting
confidence: 89%
“…Two scans were then performed; one before the injection of the LVF ("before" scan) to reflect the initial condition and another after the injection ("after" scan). In both scans, the cylinder rotated 360 degrees in the space between the X-ray source and the detector panel, yielding 625 images in 78 s. Although the cylinder is placed vertically during the X-ray CT scan, the convection due to the density difference is negligible because the scan time is shorter than that for the onset of natural convection (>500 s), estimated with the same particles [30]. Under the assumption of well-developed convection, the maximum convection travel distance during the CT scan, estimated by the product of the Darcy velocity ∆ gk/µ 1 = 1.54 × 10 −4 m/s and the CT scan time is 1.2 cm, where ∆ is the density difference between the MVF and LVF, g is the gravitational acceleration, and µ 1 is the viscosity of the injected LVF.…”
Section: Methodsmentioning
confidence: 99%
“…Whilst it may be the case the fingers reach the bottom before this happens, a lack of a constant flux was predicted from numerical simulations for Ra < 10 41,7,37 . Therefore, to compare cases, the maximum dissolution rate is used 9,38 .…”
Section: A Onset Of Convection and Dissolution Ratementioning
confidence: 99%
“…At τ = 3 − 5 the BEG fingers have penetrated further into the domain than the MEG. However, the fingers are less concentrated and are less well-defined which indicates more dispersion has occurred, and the result of high transverse and longitudinal dispersion is the quick reduction and flattening of the concentration gradients 38 . This result is consistent with previous numerical works where it has been shown that the larger the mixing zone, the closer the fingering phenomenon behaviors like a purely dispersive system 23 .…”
Section: B Plume Dynamics and Flow Structurementioning
confidence: 99%